2021
DOI: 10.1039/d1fo02040d
|View full text |Cite
|
Sign up to set email alerts
|

The short-chain fatty acid propionate improved ventricular electrical remodeling in a rat model with myocardial infarction

Abstract: Oral propionate activated vagal afferent nerve in the gut and facilitated solitary nucleus in the brain via nodose ganglia to activate vagal efferent nerve innervating the heart, so as to reduce ventricular arrhythmia after myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Changes in cardiac gap junction proteins, including the decrease of Cx43 and spatial redistribution, are characterized by abnormal electrophysiological remodeling and are referred to as representing arrhythmogenic substrates (Severs et al, 2008). Zhou et al, (2021) found that propionic acid can improve the pathological remodeling of connexin in rats with myocardial infarction. propionic acid causes the nucleus tractus solitarius in the brain through the nodular ganglia to activate vagal afferent fibers in the gut and vagal efferent neurons that innervate the heart (Dalile et al, 2019).…”
Section: Atherosclerosismentioning
confidence: 99%
“…Changes in cardiac gap junction proteins, including the decrease of Cx43 and spatial redistribution, are characterized by abnormal electrophysiological remodeling and are referred to as representing arrhythmogenic substrates (Severs et al, 2008). Zhou et al, (2021) found that propionic acid can improve the pathological remodeling of connexin in rats with myocardial infarction. propionic acid causes the nucleus tractus solitarius in the brain through the nodular ganglia to activate vagal afferent fibers in the gut and vagal efferent neurons that innervate the heart (Dalile et al, 2019).…”
Section: Atherosclerosismentioning
confidence: 99%
“…Recently, Luedde et al reported that the gut microbiome in HFpEF patients tended to have deficiencies in Ruminococcaceae and Blautia, which were SCFAs producers ( Beale et al, 2021 ). SCFAs were also beneficial to myocardial electrical remodeling for they could partly activate the parasympathetic nerves through the gut-brain axis ( Zhou et al, 2021 ). As for the underlying mechanism, Carley et al (2021) further revealed that SCFAs were efficient energy sources for HF patients because failing hearts preferred to oxidize SCFA over ketones.…”
Section: The Microbial Metabolites Associated With Heart Failurementioning
confidence: 99%
“…Ca2+ and GPR43-dependent mechanisms reduce NLRP3 inflammasome activation by acetate, thereby preventing inflammation-related arrhythmias [67]. It has also been shown that propionate prevents the development of myocardial infarction-induced ventricular arrhythmias (VA) and cardiac electrophysiological instability through parasympathetic activation based on the gut-brain axis [68].…”
Section: Arrhythmiasmentioning
confidence: 99%